1988
DOI: 10.1063/1.342064
|View full text |Cite
|
Sign up to set email alerts
|

The effects of donor dopant concentration on the grain boundary layer characteristics in n-doped BaTiO3 ceramics

Abstract: Positive temperature coefficient of resistance BaTiO3 specimens containing different donor dopant concentrations of Ho ranging from 0.05 to 1.8 at. % were investigated. The intergranular barrier layer capacitance per unit area, C′L, measured at a constant frequency of 30 kHz at both 40 and 160 °C was found to be proportional to the donor concentration up to 0.55 at. %, but then began to decrease as the donor concentration was increased beyond this. This indicated that both the density of acceptor states at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…21 Since the barrier layer is considered as a parallel-plate capacitance with an area d 2 and the same thickness as the width of the barrier layer b, we can have Ј = C L b / 0 d 2 and then 21 Since the barrier layer is considered as a parallel-plate capacitance with an area d 2 and the same thickness as the width of the barrier layer b, we can have Ј = C L b / 0 d 2 and then…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Since the barrier layer is considered as a parallel-plate capacitance with an area d 2 and the same thickness as the width of the barrier layer b, we can have Ј = C L b / 0 d 2 and then 21 Since the barrier layer is considered as a parallel-plate capacitance with an area d 2 and the same thickness as the width of the barrier layer b, we can have Ј = C L b / 0 d 2 and then…”
Section: Samplesmentioning
confidence: 99%
“…21 With g determined from the impedance spectra in Table I, N d of annealed samples can be evaluated. Assuming that is not affected by the ͑Bi 1/2 K 1/2 ͒TiO 3 addition, the value of equals 0.5 cm 2 V −1 s −1 .…”
Section: ͑8͒mentioning
confidence: 99%
“…However, it reverts to its insulating behavior and its grain size becomes very small above certain doping concentrations (about 0.4-0.5 mol%). Several researchers (like Jonker, 1) Wernicke, 2) Al-Allak et al 3) and Drofenik 4) ) have reported and explained this phenomenon by assuming a uniform distribution of dopants in the materials. A single crystal however, is semiconducting above a doping concentration of 2 mol%.…”
Section: Introductionmentioning
confidence: 98%
“…Hence, during cooling to room temperature, the material will transition from a semiconductor to a heterogeneous PTCR material, and eventually to an insulator. 183,184 Kahn confirmed this for Nb-doped BaTiO 3 cooled under different oxygen partial pressures and cooling rates. 29 This was also investigated by Sinclair's using impedance spectroscopy, which also confirmed that slower cooling resulted in a sharper and larger PTCR intensity, but also larger room temperature resisitivities.…”
Section: A Fabrication Of Ptcr Batio 3 Specimensmentioning
confidence: 63%
“…% holmium donor-doped sample in air. 184,203 According to Drofenik's model, this should be an oxidized, insulating sample. However, Huybrechts et al pointed out that the sintering temperature Al-Allak et al used was much higher 1420-1460 C compared to Drofenik's 1340 C. 12 Therefore, it is possible that the donor dopant could be incorporated without recrystallization and the reduced form was produced by equilibration at high temperature.…”
Section: Doping Concentration Grain Size and Resistivity Anomalymentioning
confidence: 99%